Beamforming Design for Dual-functional Radar-communication Systems with Holographic Metasurface Antennas - Guangyi CHEN; Ruoyu ZHANG; Hong REN; Yue MA; Chen MIAO; Wen WU (Leida xuebao, 2025)
The widespread application of wireless communication devices in emerging scenarios (e.g., Vehicle-to-Everything, Low Earth Orbit Satellites) has gradually pushed communication frequencies toward higher bands, resulting in an increasingly prominent overlap with radar frequency bands. A Dual-Functional Radar-Communication (DFRC) system, with its joint signal processing capabilities and low-power characteristics, is regarded as effective in alleviating spectrum congestion. Unlike traditional antenna array architectures, Holographic Metasurface Antennas (HMAs) embed closely arranged metamaterial units, enabling the flexible configuration of each unit’s state to regulate frequency responses. This facilitates controllable and energy-efficient beamforming, offering potential for application in DFRC systems. Considering an HMA-based DFRC system that performs target sensing in a cluttered environment while providing communication services to multiple single-antenna users, this paper formulates an optimization problem to maximize the weighted sum of communication spectral efficiency and radar mutual information, subject to constraints on the transmission power and HMA frequency response. It jointly optimizes the involved digital precoder, HMA weight matrix, and receive filter to realize an HMA-based DFRC beamforming design. To tackle this nonconvex optimization challenge, we propose an alternating optimization algorithm based on fractional programming. This algorithm first employs fractional programming techniques to transform the original problem into more manageable subproblems, which are then alternately solved using methods such as Lagrangian dual decomposition and manifold optimization. Simulation results show that the beamforming design with the HMA array architecture achieves a flexible tradeoff between communication spectral efficiency and radar mutual information performance, approaching the performance of a fully digital array architecture.